Identifikasi Kesalahan Siswa MTs Dalam Menyelesaikan Soal Teorema Pythagoras Berdasarkan Tahapan Kastolan - Gani, Moh. Rivaldi N.; Zakaria, Perry; Kobandaha, Putri Ekawaty (Jambura Journal of Mathematics Education, 2025)
The number of students who make mistakes when answering questions related to the Pythagorean Theorem is the impetus for this study, with the aim of identifying errors made by students, as well as calculating the percentage of students who make mistakes related to the Pythagorean theorem based on the Kastolan stage, where students who are the subjects of this study are class VIII students of MTs. Nurul Bahri Kabila Bone. Using quantitative descriptive research methods, data derived from the answers of 17 students were collected and analyzed using descriptive statistical analysis. Six validated description questions were used as research instruments containing questions related to the Pythagorean theorem. The results obtained the percentage of students who made Kastolan stage errors, namely: (1) conceptual errors of 52.9%, with an average of 9 students making this type of error; (2) procedural errors of 82.4%, with an average of 14 students making this type of error; and (3) technical errors of 33.3% with an average of 6 students making this type of error. The errors that obtained the largest percentage of the findings were procedural errors, with the errors encountered including students' unwillingness to solve the problem completely, not recording the known and asked information, and not concluding the answer.